The Choice of Exchange Rate Assumption in the Process of Forecasting Inflation - Tom Bernhardsen; Amund Holmsen (Norges Bank, 2005)
In the process of forecasting inflation the central bank needs to make assumptions regarding the future path of the interest rate and the exchange rate. This paper focuses on the exchange rate assumption. In particular, three alternative assumptions are discussed. First, the random walk hypothesis suggests a constant exchange rate over the forecast horizon. While being theoretically appellant and frequently chosen across central banks, the level of the exchange rate implied by the assumption remains to be determined. Moreover, assuming the exchange rate to be constant may imply a change in the real exchange rate if the inflation target differs from the target among the trading partners. Second, central banks frequently assume the exchange rate to evolve in line with uncovered interest rate parity. Combined with the assumption of using forward rates for the interest rate, this seems theoretically consistent. However, due to a possible risk premium UIP-predictions may imply a path for the exchange rate far away from market expectations, a path with which the central bank is not necessarily comfortable. Third, the central bank could base the exchange rate assumption on its best prediction of the exchange rate in the future. This would require some analytical tools for the exchange rate. In this paper we focus on mean-reversion in the real exchange rate as a guide to future nominal exchange rate movements. Exchange rate paths implied by the three alternatives are compared with actual exchange rate outcomes.
hdl:11250/2508133; Additional information: The paper was presented at the conference "Exchange rate and monetary policy", BIS 28 - 29 October 2004.
Keywords: 330